Ritual as cultural and historical practice - Pasko, Zoya (Skhid, 2013)
In the article a ritual as specific cultural and historical practice is intelligent in theory, the role of ritual is certain in becoming of man as a transmitter of cultural values, the social-communicative function of sacral activity, place of practice of ritual, is lighted up in the system of social and cultural values.